INVESTIGATION AND OPTIMIZATION OF FORMULATION PARAMETERS FOR SELFNANOEMULSIFYING DELIVERY SYSTEM OF TWO LIPOPHILIC AND GASTROINTESTINAL LABILE DRUGS USING BOX-BEHNKEN DESIGN - Kumar, Bimlesh; Garg, Varun; Singh, Amarjeet; Pandey, Narendra Kumar; Singh, Saurabh; Panchal, Sakshi; Melkani, Indu; Raji, Raji; Axel, Manzi; Mohanta, Souvik; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Present research work aims toward codelivery of two hydrophobic drugs, curcumin (CRM) and duloxetine hydrochloride (DXH) through self-nanoemulsifying drug delivery systems (SNEDDS). Methods: Initially, binary mixture in the ratio of 1:1 was prepared and then loaded into SNEDDS. Box-Behnken design (BBD) was adopted to develop SNEDDS. As per the optimal design, 13 SNEDDS prototypes were prepared. Castor oil, tween-80 and Transcutol P® were used as oil, surfactant, and cosurfactant, respectively. To 1 mL of SNEDDS, 30 mg each of CRM and DXH was loaded (CRM-DXH- SNEDDS). Results: The design revealed that for mean droplet size, polydispersity index (PDI), as well as percentage drug loading, all the three factors, i.e. ratio of oil (a), surfactant (b), and cosurfactant (c) were found to give significant effect. Factor B showed the most significant effect on mean droplet size (y1). In case of PDI (y2), factors B and C exerted maximum influence, whereas, Factor A has shown non-significant effect. For percentage drug loading of drugs (y3 and y4), all the three factors were found to have the most significant effect. The optimized batch of CRM-DXH- SNEDDS having composition castor oil, tween-80, and Transcutol P® in the ratio: 2.17:5.22:2.61, revealed that the mean drug loading (%) of CRM and DXH in an optimized batch of SNEDDS was found to be 87.22±1.87 and 92.32±0.19%, respectively. The mean droplet size, PDI, and zeta potential of formed SNEDDS were observed as 113.14±1.14 nm, 0.20±0.026, and −13.2 mV, respectively. Conclusion: BBD provided optimal formula composition for SNEDDS for obtaining desirable drug loading, emulsion droplet size, and zeta potential.